Analysis of Factors Affecting Funding Decisions at Fintech Peer-to-Peer Lending in Indonesia (Case Study on Koinworks Financial Technology) - Nadia Nurul Agustin; Syapsan Syapsan; Anthony Mayes (International Journal of Economics Development Research (IJEDR), 2023)
This study analyzes the influence of Interest Offered, Credit Class, Business Turnover, and Loan Amount on Lenders’ Fund Distribution Decisions in Fintech Peer to Peer Lending in Indonesia. This is the first empirical study using business financing submitted through the Peer-to-Peer Lending website. In this study, the data were obtained from the Koinworks.com website, a dominant Peer to Peer Lending service provider in Indonesia. Using the purposive sampling method, the sample used in this study was 88 SMEs. This study uses logistic regression using SPSS 26. The results of this study state that: (1) the interest rate offered has a significant positive effect on the decision to distribute funds; (2) credit class has a significant negative effect on the decision to distribute funds; (3) business turnover has no significant effect on the decision to distribute funds; and (4) the amount of the loan has a significant positive effect on the decision to distribute funds